PENGARUH PIJAT OKSITOSIN TERHADAP PENGELUARAN ASI PADA IBU POST PARTUM DI RUMAH SAKIT UMUM DAERAH KABUPATEN ACEH BESAR - Muna, Sirajul; Aryani, Roza; Herlita, Herlita (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Background : One of the problems in post partum mothers is the process of expressing milk because not all post partum mothers express milk after giving birth. Oxytocin massage is one of the right solutions to expedite the production and release of breast milk. Massage is carried out along the sides of the spine to the fifth and sixth costae so that it can stimulate the hormones prolactin and oxytocin so that it can facilitate the release of breast milk in post partum mothers. Research Purposes : To determine the effect of oxytocin massage on the production of breast milk in post partum mother at regional general hospital District Aceh Besar. Research Methods : This research is a pre experimental research with a one group pretest posttest design approach. The population in this study were all post partum mothers as many as 23 people with the sampling technique using simple random sampling so that the total sample was 15 people.This research was conducted on 26 September 26 – 9 October year 2022 in regional general hospital District Aceh Besar. The research instrument used was a checklist with data analysis using the wilcoxon test. Research Result : The results of the study before the oxytocin massage for post partum mothers obtained a mean value of 1,47, a standard deviation of 0,915 and a minimum and maximum value of 0 - 3. Furthermore, after the oxytocin massage was carried out for post partum mothers the mean value was 3,93, a standard deviation of 0,704 and the minimum and maximum values are 3 – 5. Then from the non parametric statistical test results namely the Wilcoxon test, it is obtained p value = 0,001. Conclusion and Recommendations: Based on the results of the study, it was found that there was an effect before and after oxytocin massage on the production of breast milk in post partum mothers. Therefore, it is hoped that post partum mothers can use oxytocin massage as an effort to expedite the release of breast milk.